EFEKTIVITAS METODE COACHING PADA PENDAMPINGAN KEWIRAUSAHAAN GUNA MENINGKATKAN KEBERHASILAN START-UP DIGITAL MAHASISWA PADA UNIVERSITAS PGRI KANJURUHAN MALANG - Jacobus Wiwin (EDU RESEARCH, 2023)
Start-up is a term for business activities or companies that are newly built or are in a pilot period. For this reason, an innovation is needed to increase digital start-ups in students, one of which is by using coaching. Coaching is an integrative activity in entrepreneurship assistance. Together with mentoring, counselling, and other elements, it will greatly affect the achievement of Coaching quality in entrepreneurship mentoring to increase the success of student digital startups at Universitas PGRI Kanjuruhan Malang. This study was conducted on entrepreneurship mentoring to improve the success of student digital starups at Universitas PGRI Kanjuruhan Malang. To obtain the data needed in this study, the authors used several data collection methods commonly used in a research process, including observation, questionnaires, and interviews. In its current implementation, the Coaching process in entrepreneurship mentoring to increase the success of student digital startups at Universitas PGRI Kanjuruhan Malang is constrained by several limitations. Coaching is an integrative activity in entrepreneurship mentoring. Together with mentoring, counselling, and other elements will greatly affect the achievement of quality Coaching in entrepreneurship mentoring can increase the success of student digital starups at PGRI Kanjuruhan University Malang. This can be seen from the percentage results that have been obtained based on the results of the data analysis above. With a percentage of 100% in the process and relationship, while the structure and focus are at 66.67% and the last is 33.33 for diagnostic tools.